Advertising strategies as a means of influencing existing and potential buyers of advertised products - Babina, Julia; Bebko, Svitlana (My University, 2019)
The notion of advertising strategy has been considered. There has been studied the opportunities of using an advertising strategy at an enterprise. The advantages and disadvantages of using an advertising strategy have been analyzed.
Keywords: advertising strategies; potential buyers; consumers; advertised products; рекламні стратегії; потенційні покупці; споживачі; рекламована продукція; кафедра ділової іноземної мови та міжнародної комунікації